Perancangan Template Video Profil Sebagai Media Promosi dengan Teknik Motion Graphic - Wynni Safenthi (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
This research aims as one of the tools to promote Fitness and Gymnastics GOR Bimo Seno using multimedia products in the form of promotional videos through social media. In making this thesis, researchers used qualitative methods and SWOT analysis methods. Fitness and Gymnastics GOR Bimo Seno does not have adequate promotional media, causing Fitness and Gymnastics to experience a decrease in visitors and is still poorly known in the community of Masaran district. Therefore, modern promotional media is needed. Which in the application of multimedia, especially Motion Graphics, is very developed, especially in the field of promotion used in companies in the era of modernization and all digitan like today. This promotional video is expected to have a positive impact on companies and communities in the masaran district and surrounding areas in the form of promotional videos by displaying existing facilities and services provided by Fitness and Gymnastics GOR Bimo Seno.